2021
DOI: 10.3390/ani11102792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calving Difficulties and Calf Mortality on Functional Longevity in Polish Holstein-Friesian Cows

Abstract: Longevity is one of the functional traits that considerably affect dairy herd profitability. A Weibull proportional hazards model was used to evaluate the impact of difficult calvings and calf stillbirths on cow functional longevity, defined as length of productive life corrected for milk production. The data for analysis comprised calving ease and calf mortality scores of 2,163,426 calvings, 34.4% of which came from primiparous cows. The percentage of male calves was 53.4%. Calving ease was scored as “without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
4
12
2
Order By: Relevance
“…An increased percentage of milk fat was related to the higher culling risk for most culling categories, especially in the second and third lactations. A similar advantageous effect of protein content and a more neutral influence of fat content on the culling rate was found by Sasaki et al [ 110 ], Chirinos et al [ 111 ], and Morek-Kopeć et al [ 109 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…An increased percentage of milk fat was related to the higher culling risk for most culling categories, especially in the second and third lactations. A similar advantageous effect of protein content and a more neutral influence of fat content on the culling rate was found by Sasaki et al [ 110 ], Chirinos et al [ 111 ], and Morek-Kopeć et al [ 109 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, the HR value for the percentage of milk protein was below unity for almost all culling categories, which suggested a decreased culling risk. A similar effect of increased milk protein content on culling rate was observed by Morek-Kopeć et al [ 109 ], indicating that a lower protein content associated with the lactation stage and difficult calving may contribute to the culling of a cow. An increased percentage of milk fat was related to the higher culling risk for most culling categories, especially in the second and third lactations.…”
Section: Discussionsupporting
confidence: 75%
“…The percentage of male and female calves in this study was 50.5% and 49.5%, respectively, and male calves were more likely to be stillborn, which is consistent with the results of Maltecca et al 59 that male calves have a higher risk of stillbirth than female calves. According to a recent study, the stillbirth rate for male calves (7.7%) was more than twice as high as that of female calves (3.7%) 60 . Mellado et al 61 found that calves with a birth weight of < 35 kg had the highest probability of stillbirth, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent research, Morek-Kopec et al (2021) [19] reported for Polish Holstein Friesian cows that stillbirth rate from male calves at calving was 7.7% and for female calves 3.7%.…”
Section: Discussionmentioning
confidence: 98%